2023
DOI: 10.1007/s42161-022-01299-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and comparisons of potato wart (Synchytrium endobioticum) in historic collections to recent findings in Canada and the Netherlands

Abstract: Synchytrium endobioticum (Schilb.) Perc. is a chytrid fungus causing potato wart disease and is one of the most important quarantine diseases on cultivated potato. Infected host tissues develop warts rendering the crop unmarketable. Resting spores, that can remain viable and infectious for decades, are formed in warted tissues and are released into the surrounding soil when host tissue decays.To better understand the pathogen’s diversity and to potentially uncover pathways of migrations and introduction events… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 34 publications
(23 reference statements)
2
10
1
Order By: Relevance
“…Resting spores were isolated from 200 g compost, which serve as inoculum for bio-assays, from the NPPO-NL S . endobioticum collection with a zonal centrifuge as described previously [ 5 ]. For the Canadian material, resting spores were collected in sieves, washed, and centrifuged, as described previously [ 8 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Resting spores were isolated from 200 g compost, which serve as inoculum for bio-assays, from the NPPO-NL S . endobioticum collection with a zonal centrifuge as described previously [ 5 ]. For the Canadian material, resting spores were collected in sieves, washed, and centrifuged, as described previously [ 8 10 ].…”
Section: Methodsmentioning
confidence: 99%
“… a SendoTrack-ID from [ 5 ] b C q values of the SSU TaqMan assay from [ 12 ], NA = not applicable or not done. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, two complete genomes and partial genomic and transcriptomic datasets have been published for S. endobioticum, with assembly sizes of 21.48 and 23.21 Mb [ 17 ]. Along with the published nuclear genomes, the structure of the mitochondrial genome, a most likely maternally inherited linear molecule of 72.9 Kbp, has been published, and comparative analyses with the mt genomes of a number of genotypes have been performed [ 18 , 19 ]. These studies showed considerable variation between mitogenomes, with six different haplotypes identified, as well as putative admixtures in some of the populations studied.…”
Section: Introductionmentioning
confidence: 99%